2012
DOI: 10.1177/1076029612454935
|View full text |Cite
|
Sign up to set email alerts
|

Progressive Increase of Inflammatory Biomarkers in Chronic Kidney Disease and End-Stage Renal Disease

Abstract: Chronic kidney disease (CKD) has reached epidemic levels. It is a multisystem disease associated with elevated systemic inflammatory and hypercoagulable states. Most concerning are the cardiovascular risks associated with all stages of kidney disease. It is difficult to assess kidney disease stage progression and cardiovascular risk with current indicators such as estimated glomerular filtration rate and conventional cardiovascular risk factors. However, the use of biomarkers to assess the underlying pathologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 28 publications
2
24
0
Order By: Relevance
“…Additional risks have been attributed to the presence of nontraditional risk factors, such as inflammation, which have been shown to promote proliferation and infiltration of inflammatory cells into the tunica intima of small arteries, leading to the development of atherosclerosis and stenosis [10]. An association between a decline in RRF in patients with CKD and progressively increased level of systemic inflammatory burden which is most marked in those receiving renal replacement therapy, such as haemodialysis, has been well established [11, 12]. At present, there is no clear evidence to suggest any significant difference in the systemic inflammatory burden based on the type of dialysis modality received (i.e., haemodialysis versus peritoneal dialysis) [13].…”
Section: Introductionmentioning
confidence: 99%
“…Additional risks have been attributed to the presence of nontraditional risk factors, such as inflammation, which have been shown to promote proliferation and infiltration of inflammatory cells into the tunica intima of small arteries, leading to the development of atherosclerosis and stenosis [10]. An association between a decline in RRF in patients with CKD and progressively increased level of systemic inflammatory burden which is most marked in those receiving renal replacement therapy, such as haemodialysis, has been well established [11, 12]. At present, there is no clear evidence to suggest any significant difference in the systemic inflammatory burden based on the type of dialysis modality received (i.e., haemodialysis versus peritoneal dialysis) [13].…”
Section: Introductionmentioning
confidence: 99%
“…The main finding of our study, conducted in a large, hospital‐based dialysis center, is that the prevalence of positive D‐dimer values is high not only in the general hemodialysis population (75% of positive values), but also in patients without additional acute or chronic predisposing disease (52% of positive values), which limits its usefulness for exclusion of VTE in everyday clinical practice. Several previous studies have shown that patients with chronic kidney disease not on dialysis have higher D‐dimer values than healthy population, but still within normal range, and that D‐dimer levels correlate with the level of renal function . In dialysis patients, a high prevalence of positive values was reported in patients without symptoms of VTE .…”
Section: Discussionmentioning
confidence: 97%
“…Several previous studies have shown that patients with chronic kidney disease not on dialysis have higher D-dimer values than healthy population, but still within normal range, and that D-dimer levels correlate with the level of renal function. 10,11 In dialysis patients, a high prevalence of positive values was reported in patients without symptoms of VTE. 12 Furthermore, in a study of patients referred to computed tomography angiography to rule out pulmonary embolism, none of the 29 patients with eGFR <30 mL/min had a negative D-dimer, although in only 17% of them pulmonary embolism was confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, soluble TM (sTM) identifiable in plasma not only reflects endothelial injury, but also inflammation [30]. Nevertheless, the clinical predictive value of sTM has been reported in sepsis [31], metabolic syndrome [32] and chronic kidney disease [33].…”
Section: Biomarkers Of the Endothelial Dysfunctionmentioning
confidence: 99%